Neurosyphilis-Induced Psychosis in Europe: A Systematic Review of Case Reports - Adam Jarocki; Kinga Klimczyk; Monika E. Łysakowska; Filip Bielec; Dorota Pastuszak-Lewandoska (Pathogens)
The tertiary stage of syphilis appears to be the most diverse of the three recognized, with a number of cardiovascular, gummatous, neurological and psychiatric symptoms. This systematic review’s aim is to analyze cases of organic psychoses secondary to tertiary syphilis, inspect the diagnostic procedures and assess the effectiveness of treatment. Case studies from Pubmed and MEDLINE Ultimate were sought out with the Boolean expression ‘((neurosyphilis) OR (syphilis) OR (treponema pallidum)) AND (case report) AND ((psychosis) OR (psychotic))’ to later undergo screening for exclusion criteria (according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) 2020 guidelines). Each report was accepted independently by two authors. Case reports were later appraised using the JBI Critical Appraisal Checklist for Case Reports. Finally, 11 case reports were included in the study. The most frequently reported psychiatric symptoms were delusions (91%) and hallucinations (81%), disorientation (about 42%) and sleep disturbances and memory loss (36%). Several inconsistencies in diagnostic processes were found in some of the case reports, while treatment procedures were more in line with the guidelines. A disease as complex as neurosyphilis requires great awareness and cooperation between various medical specialties. Despite its mimicry and variability in presentation, the discussed case reports prove that it can be successfully dealt with.